2013
DOI: 10.1007/s10144-013-0398-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that livestock grazing intensity affects cyclic vole population regulation processes

Abstract: Grazing by domestic ungulates may limit the densities of small herbivorous mammals that act as key prey in ecosystems. Whether this also influences density dependence and the regulation of small herbivore populations, hence their propensity to exhibit multi-annual population cycles, is unknown. Here, we combine time series analysis with a large-scale grazing experiment on upland grasslands to examine the effects of livestock grazing intensity on the population dynamics of field voles (Microtus agrestis). Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Vole density and cycle amplitude.-First, to test for a long-term response of vole density to grazing intensity, the proportion of positive VSI was modelled as a function of treatment, with year as an additive explanatory covariate in order to account for some degree of background synchrony in peaks and troughs across treatments detected in previous analyses (Villar et al 2013a), and season to account for seasonality in vole density. Second, to test the effect of grazing intensity on the amplitude of vole density fluctuations, we first derived cycle amplitude as the 10th to 90th inter-quantile range of time series of VSI scores (VSI inter-quantile; Cornulier et al 2013) for each experimental plot separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vole density and cycle amplitude.-First, to test for a long-term response of vole density to grazing intensity, the proportion of positive VSI was modelled as a function of treatment, with year as an additive explanatory covariate in order to account for some degree of background synchrony in peaks and troughs across treatments detected in previous analyses (Villar et al 2013a), and season to account for seasonality in vole density. Second, to test the effect of grazing intensity on the amplitude of vole density fluctuations, we first derived cycle amplitude as the 10th to 90th inter-quantile range of time series of VSI scores (VSI inter-quantile; Cornulier et al 2013) for each experimental plot separately.…”
Section: Discussionmentioning
confidence: 99%
“…In our experimental system, vole populations exhibit cycles with periodic multi-annual peaks and troughs in abundance, which are affected by grazing (Villar et al 2013a). It is thought that both mean abundance and amplitude in rodent cycles are critical factors for sustaining populations of endangered carnivore predators in similar grassland systems at higher latitudes, leading to cyclical pulses in survival and reproduction in such predators (Sundell et al 2004, Henden et al 2008.…”
Section: Introductionmentioning
confidence: 97%
“…A1). Each plot was scanned for signs indicating the presence of voles: runways, fresh plant fragments, or faecal pellets (see Villar et al, 2014). For analysis, the proportion of subplots with vole presence was calculated per paddock (N = 3 replicates per treatment).…”
Section: Volesmentioning
confidence: 99%
“…Grazing is often beneficial to plant species richness (Olff and Ritchie, 1998), but detrimental to species richness of many arthropod groups (Foster et al, 2014;, molluscs (Boschi and Baur, 2007) and small mammals (e.g. Villar et al, 2014), while mixed effects are reported for species richness of meadow birds (e.g. Atkinson et al, 2005;WallisDeVries et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation